2017
DOI: 10.3390/catal7090244
|View full text |Cite
|
Sign up to set email alerts
|

DBD Plasma Assisted CO2 Decomposition: Influence of Diluent Gases

Abstract: Carbon dioxide (CO 2 ) partial reduction to carbon monoxide (CO) and oxygen has been conducted in a dielectric barrier discharge reactor (DBD) operating a packed bed configuration and the results are compared with that of no packing condition. The effect of diluent gas is studied to understand the influence on dielectric strength of the plasma gas on CO 2 splitting, with the objective of obtaining the best CO selectivity and high energy efficiency. Typical results indicated that among N 2 , He and Ar gases, Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(17 citation statements)
references
References 32 publications
(46 reference statements)
0
17
0
Order By: Relevance
“…Figure 9 shows a schematic process for the plasma surface modification of PTFE membranes. Moreover, based on our experiment results as well as relevant literatures on surface modification using plasma-based technique [35,36], a hypothesized mechanism is presented in Figure S4 to illustrate how AAc molecules are grafted on the surface of the PTFE membranes in CO2 plasma. To further explore the versatility of the demonstrated plasma modification technique, a series of substrates including polyethylene (PE) membrane, polyvinylidene fluoride (PVDF) membrane, and plexiglass plate are used.…”
Section: Resultsmentioning
confidence: 86%
“…Figure 9 shows a schematic process for the plasma surface modification of PTFE membranes. Moreover, based on our experiment results as well as relevant literatures on surface modification using plasma-based technique [35,36], a hypothesized mechanism is presented in Figure S4 to illustrate how AAc molecules are grafted on the surface of the PTFE membranes in CO2 plasma. To further explore the versatility of the demonstrated plasma modification technique, a series of substrates including polyethylene (PE) membrane, polyvinylidene fluoride (PVDF) membrane, and plexiglass plate are used.…”
Section: Resultsmentioning
confidence: 86%
“…In effect, NTP decomposes CO 2 into carbon monoxide (CO) and oxygen (O 2 ) with the use of Ar as a diluent gas . Alternatively, other studies have shown the possibility to perform the process in a nitrogen (N 2 ) environment, resulting in an overall lower cost . Subsequently, the CO produced is usually coupled with a hydrogen source (H 2 ) to produce syngas (CH 4 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Several NTP configurations such as glow discharge, gliding arc discharge, corona discharge, and dielectric barrier discharge (DBD) were reported for various applications. NTP was widely tested for methanol production, syngas synthesis, wastewater treatment, , and carbon dioxide decomposition. Among various NTP configurations, DBD has withdrawn special consideration due to advantages like (i) generation of high energetic electrons (1–10 eV), (ii) ability to initiate the chemical reaction at atmospheric pressure and temperature, (iii) offering high electron energy density, etc. ,, However, DBD alone is not good enough to improve the selectivity of desired products, and hence catalyst integration is necessary. So far, researchers investigated the DRM reaction using novel metal-based (Ru, Pd, Pt, and Rh) ,, and transition metal-based (Co, Ni, and Fe) , catalysts.…”
Section: Introductionmentioning
confidence: 99%